2012
DOI: 10.1371/journal.pone.0029652
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Therapy and Outcomes of Patients with Pneumonia Caused by Influenza A Pandemic (H1N1) Virus

Abstract: BackgroundThere is limited data on the clinical outcome of patients with pandemic H1N1 (pH1N1) pneumonia who received oseltamivir treatment, especially when the treatment was administered more than 48 hours after symptom onset.MethodsDuring the pandemic in 2009, a cohort of pH1N1 influenza pneumonia was built in China, and their clinical information was collected systematically, and analyzed with Cox models.Results920 adults and 541 children with pneumonia who didn't receive corticosteroids were analyzed. In-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 21 publications
4
54
0
2
Order By: Relevance
“…Of note, delayed oseltamivir therapy was significantly found in patients with lung involvement. In consistent with previous reports, 35 , 40 , 41 our data recommended an early treatment with oseltamivir for patients whenever 2009 pandemic influenza A (H1N1) is diagnosed or epidemiologically suspected, regardless of age, and this may be particularly important for those with pulmonary involvement.…”
Section: Discussionsupporting
confidence: 91%
“…Of note, delayed oseltamivir therapy was significantly found in patients with lung involvement. In consistent with previous reports, 35 , 40 , 41 our data recommended an early treatment with oseltamivir for patients whenever 2009 pandemic influenza A (H1N1) is diagnosed or epidemiologically suspected, regardless of age, and this may be particularly important for those with pulmonary involvement.…”
Section: Discussionsupporting
confidence: 91%
“…Although all 30 studies classified patients by treatment exposure, only two defined it: one as 'at least one dose of oseltamivir' 181 and the other as 'at least one day of treatment' 182 [although it was unclear how they classified patients who received one dose only; there were 26 such patients excluded from the study [Iratxe Puebla, PLOS ONE journal editor, 7 August 2012, personal e-mail communication)]. It is unknown how many other studies failed to report excluded patients but we note that a number of studies had missing information on mortality status and/or treatment status (for 200 patients in one study, 183 for which missing data were more common in patients with less-severe disease), whereas other studies reported complete information.…”
Section: Quality Of the Included Studiesmentioning
confidence: 99%
“…In addition, patients who are extremely sick may not be given the opportunity to receive treatment because other more critical procedures take priority. Only two of the included studies 182,184 attempted to take account of time-dependent bias but they appeared to have used flawed approaches. One study excluded all deaths within 3 days of onset of symptoms and the other obtained results that appear incorrect because their analysis -taking into account time-dependent bias -increased the treatment effect in favour of oseltamivir.…”
Section: Quality Of the Included Studiesmentioning
confidence: 99%
“…To our knowledge, this is the first recorded case of fungal spondylodiscitis found in a patient recovered from H7N9 infection. As outbreaks of H7N9 and other avian influenza virus infections increase worldwide (Liem et al, 2009;Yang et al, 2012;Chen et al, 2013;Gao et al, 2013;Uyeki and Cox, 2013), we should keep in mind that patients infected by such viruses may suffer from fungal spondylodiscitis, even after recovery from the viral infection.…”
Section: Discussionmentioning
confidence: 99%